Identification of measles virus genotype B3 associated with outbreaks in Islamabad, Pakistan, 2013-2015 - Syed S.Z. Zaidi; Abdul Hameed; Muhammad Suleman Rana; Muhammad M. Alam; Massab Umair; Uzma B. Aamir; Maqbool Hussain; Salmaan Sharif; Shahzad Shaukat; Mehar Angez; Adnan Khurshid (Elsevier, 2018)
Background: Measles virus infection remains a significant cause of childhood mortality and morbidity despite continued global efforts and the availability of a safe and effective vaccine. Molecular analysis of indigenous measles viruses could provide critical information on outbreak linkages and transmission pathways that can aid the implementation of appropriate control programs in Pakistan. Methods: Blood samples and throat swabs were collected from subjects suspected with measles in Islamabad, Pakistan from 2013 to 2015. Serum samples were tested for the presence of measles immunoglobulin M (IgM) antibodies using enzyme-linked immunosorbent assay (ELISA) while throat swabs were used for the isolation (Vero/SLAM cell line) and subsequent characterization and phylogenetic analysis of measles strains. Results: Of 373 blood samples, 66% tested positive for measles IgM. Male subjects were more often infected (58%) than female (42%) with the highest frequency of positive cases (63%) in the 0-5-years age group. Among the positive cases, only 13% had received one or two doses of the measles vaccine, while 87% were unvaccinated. Of 80 throat swabs, 29 (36%) showed a measles virus-specific cytopathic effect (CPE) and were characterized as genotype B3 through partial sequencing of the nucleoprotein (N) gene. Phylogenetic analysis revealed the Pakistani B3 strains to be closely related to strains from neighboring countries (Iran and Afghanistan) as well as with B3 viruses from the USA, Germany, and the UK. Conclusions: The study results showed that despite the availability of an effective vaccine, the burden of measles infections is very high in Pakistan due to poor routine immunization coverage even in major cities, including the capital city of Islamabad. It is imperative that national health authorities take urgent strategic steps to improve routine immunization and implement adequate molecular identification methods to tackle future measles outbreaks. Keywords: Measles virus, Epidemiology, Outbreak